Enhancing Employability Skills through Infosys Campus Connect Programme:A Case Study - Balasubramani, R.; ., Devidas (Journal of Engineering Education Transformations, 2015)
Enhancing the employability skills of the graduates is the need of the hour for every engineering education institute. To improve the employability skills, every institute follows their own method. Providing soft skills&technical skills training, arranging lectures by industry&academic experts, training students for global certifications etc. are few of the methods. In this paper, we discuss our institute's association with Infosys through their Campus Connect Programme, which has immensely benefited out students to become industry ready. Also, we discuss the ways how Infosys addresses the requirements of faculty and students. We strongly believe that effective implementation of Infosys Campus Connect programme will bridge the gap between our academic outputs and the industry requirements.